2012
DOI: 10.1093/jxb/ers076
|View full text |Cite
|
Sign up to set email alerts
|

Low relative humidity triggers RNA-directed de novo DNA methylation and suppression of genes controlling stomatal development

Abstract: Environmental cues influence the development of stomata on the leaf epidermis, and allow plants to exert plasticity in leaf stomatal abundance in response to the prevailing growing conditions. It is reported that Arabidopsis thaliana ‘Landsberg erecta’ plants grown under low relative humidity have a reduced stomatal index and that two genes in the stomatal development pathway, SPEECHLESS and FAMA, become de novo cytosine methylated and transcriptionally repressed. These environmentally-induced epigenetic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 82 publications
5
102
2
3
Order By: Relevance
“…6, A and B). Interestingly, both loci were found to be largely devoid of DNA methylation across all experimental samples, comparable to the unmethylated nonstressed plants reported previously (Tricker et al, 2012). However, there was no evidence of any transmissible hypermethylation at these loci, neither lineage dependent nor drought dependent.…”
Section: Negligible Dna Methylome Epi-alleles Associated With Transgesupporting
confidence: 81%
See 2 more Smart Citations
“…6, A and B). Interestingly, both loci were found to be largely devoid of DNA methylation across all experimental samples, comparable to the unmethylated nonstressed plants reported previously (Tricker et al, 2012). However, there was no evidence of any transmissible hypermethylation at these loci, neither lineage dependent nor drought dependent.…”
Section: Negligible Dna Methylome Epi-alleles Associated With Transgesupporting
confidence: 81%
“…One of the key responses to drought stress is stomatal closure (Verslues et al, 2006), and recent investigations have found that environmentally induced variation in stomatal development and index is regulated, at least in part, by DNA methylation, with some evidence for DNA methylation-mediated transgenerational transmission (Tricker et al, 2012(Tricker et al, , 2013. Greater stomatal control to prevent dehydration would be beneficial under water limitation; therefore, stomatal responsiveness was compared between lineages.…”
Section: Drought-exposed Lineages Exhibit Enhanced Seed Dormancymentioning
confidence: 99%
See 1 more Smart Citation
“…Farquhar, 2001). The regulation of stomatal movement is coordinately controlled by a large network of signaling pathways that monitor water status, light, CO 2 and various other environmental conditions to optimize plant growth and water use (Schroeder et al, 2001;Shimazaki et al, 2007;Casson and Hetherington, 2010;Tricker et al, 2012). Numerous Arabidopsis mutants have been isolated that are defective in stomatal function (Gray et al, 2000;Assmann, 2003;Miyazawa et al, 2006;Young et al, 2006;Kang et al, 2009a;Clark et al, 2011;Sawinski et al, 2013).…”
Section: Stomata Structure and Functionmentioning
confidence: 99%
“…RdDM is also required for basal heat tolerance in Arabidopsis (Popova et al, 2013). Environmental stresses trigger the expression of siRNAs that modulate target genes involved in the stress response (Tricker et al, 2012;Wang et al, 2015). RdDM-associated siRNAs can also defend the genome from heat-induced movements of TEs (Ito et al, 2011).…”
mentioning
confidence: 99%